The Decline in German Output Volatility: A Bayesian Analysis - Roman Liesenfeld; Jens Hogrefe; Christian Aßmann (Kiel University, Department of Economics, 2005)
Empirical evidence suggests a sharp volatility decline of the growth in U.S. gross domestic product (GDP) in the mid-1980s. Using Bayesian methods, we analyze whether a volatility reduction can also be detected for the German GDP. Since statistical inference for volatility processes critically depends on the specification of the conditional mean we assume for our volatility analysis different time series models for GDP growth. We find across all specifications evidence for an output stabilization around 1993, after the downturn following the boom associated with the German reunification. However, the different GDP models lead to alternative characterizations of this stabilization : In a linear AR model it shows up as smaller shocks hitting the economy, while regime switching models reveal as further sources for a stabilization, a narrowing gap between growth rates during booms and recessions or flatter trajectories characterizing the GDP growth rates. Furthermore, it appears that the reunification interrupted an output stabilization emerging already around 1987.
Keywords: C11; C15; C32; E32; 330; business cycle models; Gibbs sampling; Markov Chain Monte Carlo; regime switching; structural breaks; Konjunktur; Sozialprodukt; Volatilität; Zeitreihenanalyse; Schätzung; Deutschland